Physical variables - stream additional logger system from Miellejohka, 383 m a.s.l., 2016-09-26–2022-11-24 - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2026)
High frequency additional logger system measurements of CO2 and O2 in streams.
Abisko Scientific Research Station (2026). Physical variables - stream additional logger system from Miellejohka, 383 m a.s.l., 2016-09-26–2022-11-24 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/2G748DfU6Zk_MqSOITXOtHl3
Keywords: Abisko Scientific Research Station; Stream; Time instant; Time instant; Dissolved oxygen; Dissolved oxygen; Water temperature; Water temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap